A Study of Plant and Equipment Utilization on Selected Construction Sites in Lagos State - Akinola, Joseph Aderemi (2015)
The study examined the level of utilization of plant and equipment and its impacts on site operations in Lagos State with a view to optimising output levels on construction sites.